2023
DOI: 10.7759/cureus.43555
|View full text |Cite
|
Sign up to set email alerts
|

Role of microglia in neuropathic pain

Abstract: Microglial cells are specialized macrophage cells of the central nervous system responsible for the innate immunity of the spinal cord and the brain. They protect the brain and spinal cord from invaders, microbes, demyelination, trauma and remove defective cells and neurons. For immune protection, microglial cells possess a significant number of receptors and chemical mediators that allow them to communicate rapidly and specifically with all cells of the nervous tissue. The contribution of microglia in neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Participation of spinal astrocytes and microglia in the modulation of pain processing, however, can profoundly be influenced by their expression profiles. Reactive glia can release a set of inflammatory mediators including TNFα and IL-1β which can directly drive the development of central sensitization and a consequent persistent pain ( Tang et al, 2021 ; Karavis et al, 2023 ). Our data confirmed that neuroinflammatory astrocytes and microglia in the SDH in vivo and in vitro increase the expression of COX-2 resulting in an increased capacity for the oxygenation of arachidonic acid derivatives including 2-AG.…”
Section: Discussionmentioning
confidence: 99%
“…Participation of spinal astrocytes and microglia in the modulation of pain processing, however, can profoundly be influenced by their expression profiles. Reactive glia can release a set of inflammatory mediators including TNFα and IL-1β which can directly drive the development of central sensitization and a consequent persistent pain ( Tang et al, 2021 ; Karavis et al, 2023 ). Our data confirmed that neuroinflammatory astrocytes and microglia in the SDH in vivo and in vitro increase the expression of COX-2 resulting in an increased capacity for the oxygenation of arachidonic acid derivatives including 2-AG.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation can arise from a variety of sources most notably via transcription/translation of inflammatory mediators from the nucleus of the cell which ultimately lead to activated microgliosis. Microgliosis is a central hallmark of neuropathic pain where the amoeboid activated proinflammatory M1 phenotypic state has been implicated in the development and progression of neuropathic pain ( Karavis et al, 2023 ). Peroxisome proliferator-activated receptor gamma (PPAR γ), a member of a large group of nuclear receptors controlling the proliferation of peroxisomes has been shown to have anti-inflammatory functions in several macrophagous cell types (references in Li et al via inhibition of microglia activation and ultimately reduction in neuroinflammation).…”
mentioning
confidence: 99%